Finite Math and Applied Calculus (6th Edition)

Published by Brooks Cole
ISBN 10: 1133607705
ISBN 13: 978-1-13360-770-0

Chapter 0 - Section 0.3 - Multiplying and Factoring Algebraic Expressions - Exercises: 40

Answer

$y=3$ or $y=-\frac{1}{3}$

Work Step by Step

$3y^{2}-8y-3$ =$3y^{2} - 9y + y -3$ =$3y(y-3)+1(y-3)$ $(y-3)(3y+1)$$=0$ $y=3$ or $y=-\frac{1}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.